THE EFFECT OF NIMODIPINE ON CALCIUM INTRACELLULAR AND ROS EXPRESSION IN NEURON CULTURE CELL LINE SH-SY5Y INDUCE CHRONIC HIPERGLYCEMIA - Kurniawan, Shahdevi Nandar; Kandhisa; Arisetianto, Catur; Setijowati, Nanik (International Journal of Research -GRANTHAALAYAH, 2020)
Introduction: A frequent microvascular complication of diabetes mellitus were peripheral neuropathies with a prevalence of around 30-50%. Generally, oxidative stress is the key to the pathological process that induces damage to peripheral nerves in sensory neurons thereby increasing the production of reactive oxygen species (ROS) and mitochondrial dysfunction which causes deregulation of calcium ion homeostasis and disrupted calcium signaling. Nimodipine is an L-type Ca2+ inhibitor that reactivates the ATPase pathway, has a neuroprotective effect and can improve the regulation of blood and nerve flow in restoring the adrenergic function of the vasa nervorum. Aim: The purpose of this study was to determine the effect of 0.5µm nimodipine on intracellular calcium and ROS expression in SH-SY5Y cell cultures induces chronic hyperglycemia. Method: Normoglycemic glucose-induced cell culture of neurons 25mM, 50mM hyperglycemia for 6 days and then given nimodipine and without 0.5µM nimodipine. Results: Based on the results of the One-Way ANOVA test, there was a significant difference (p<0.05) in intracellular calcium expression and ROS in cell cultures exposed to chronic hyperglycemia. Nimodipine 0.5µM significantly reduced intracellular calcium expression but did not reduce ROS expression. The Spearman rank correlation test (r=0.5; p>0.05) given nimodipine 0.5µM therapy found a positive correlation, but not significant. Conclusion: Based on this study it can be concluded that the administration of 0.5µM nimodipine can reduce intracellular calcium expression but has not been able to reduce ROS expression in 50mM glucose-induced cell cultures.